2013
DOI: 10.5402/2013/945853
|View full text |Cite
|
Sign up to set email alerts
|

Practice Trends in the Surgical Management of Renal Tumors in an Academic Medical Center in the Past Decade

Abstract: Objectives. To evaluate the trends of surgical treatment of the renal tumor in an academic medical center. Methods. Between 2001 and 2010, 505 were treated surgically at the Federal University of Sao Paulo for renal tumors. The following variables were observed and analyzed according to their evolution through time: frequency and types of surgeries performed, operative time, hospital stay, and warm ischemia time for partial nephrectomy.Results. An increase in the frequency of laparoscopic radical nephrectomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Matheus et al in a case series of 505 patients also reported similar findings. 17 The surgical complications were graded according to the Clavien-dindo system. Three patients in the laparoscopic group developed complications whereas 5 patients developed complications in the open approach, however, this is not statistically significant (P-value = 0.230).…”
Section: Discussionmentioning
confidence: 99%
“…Matheus et al in a case series of 505 patients also reported similar findings. 17 The surgical complications were graded according to the Clavien-dindo system. Three patients in the laparoscopic group developed complications whereas 5 patients developed complications in the open approach, however, this is not statistically significant (P-value = 0.230).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 505 patients from brazil reported that the average age, operative time, hospital stay, and renal tumor size were 56 years (17–84), 190.3 min (55–630), 4.7 days (1–60), and 5.9 cm (0.5–28), respectively. [ 38 ] Their results showed there was a significant decrease in operative time, length of hospital stay, and tumor size when comparing laparoscopy to open surgeries between the periods of 2001 to 2005 and 2006 to 2010. And these three variables in our data show a similar pattern of results.…”
Section: Discussionmentioning
confidence: 99%